2019
DOI: 10.48550/arxiv.1910.13573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semi-Supervised Natural Language Approach for Fine-Grained Classification of Medical Reports

Abstract: Although machine learning has become a powerful tool to augment doctors in clinical analysis, the immense amount of labeled data that is necessary to train supervised learning approaches burdens each development task as time and resource intensive. The vast majority of dense clinical information is stored in written reports, detailing pertinent patient information. The challenge with utilizing natural language data for standard model development is due to the complex and unstructured nature of the modality. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Banerjee et al [Banerjee et al, 2017] found that there was not much difference between a uni-gram approach and a Word2vec embedding, hypothesising this was due to their narrow domain, intracranial haemorrhage. However, the NLP research field has seen a move towards bi-directional encoder representations from transformers (BERT) based embedding models not reflected in our analysis, with only one study using BERT generated embeddings [Deshmukh et al, 2019]. Embeddings from BERT are thought to be superior as they can deliver better contextual representations and result in improved task performance.…”
Section: Clinical Applications and Nlp Methods In Radiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Banerjee et al [Banerjee et al, 2017] found that there was not much difference between a uni-gram approach and a Word2vec embedding, hypothesising this was due to their narrow domain, intracranial haemorrhage. However, the NLP research field has seen a move towards bi-directional encoder representations from transformers (BERT) based embedding models not reflected in our analysis, with only one study using BERT generated embeddings [Deshmukh et al, 2019]. Embeddings from BERT are thought to be superior as they can deliver better contextual representations and result in improved task performance.…”
Section: Clinical Applications and Nlp Methods In Radiologymentioning
confidence: 99%
“…This category was not found in Pons' work. Methods considered a range of conditions including intracranial haemorrhage [Jnawali et al, 2019, Banerjee et al, 2017, aneurysms [K los et al, 2018], brain metastases [Deshmukh et al, 2019], ischaemic stroke , Garg et al, 2019, and several classified on types and severity of conditions e.g., [Deshmukh et al, 2019, Shin et al, 2017, Wheater et al, 2019, Gorinski et al, 2019. Studies focused on breast imaging considered aspects such as predicting lesion malignancy from BI-RADS descriptors [Bozkurt et al, 2016], breast cancer subtypes [Patel et al, 2017], and extracting or inferring BI-RADS categories, such as [Banerjee et al, 2019a, Miao et al, 2018.…”
Section: Disease Information and Classificationmentioning
confidence: 99%